Urgensi Kewenangan Constitutional Complaint dalam Penguatan Hak-Hak Konstitusional - Fitri Sakinah, Afifah; Wijayanti, Septi Nur (Universitas Muhammadiyah Yogyakarta, 2024)
The idea of ​​the urgency of constitutional complaint authority to the Constitutional Court is part of an effort to protect the rights of citizens protected by the 1945 Constitution. This arose because the constitutional rights of citizens are often violated by various parties, including non-compliance of state administrators and abuse of authority in the executive, legislative and judicial realms. This study discusses the urgency of constitutional complaint authority for strengthening constitutional rights in the Constitutional Court of the Republic of Indonesia. The method used in this study is descriptive analytical research using a normative legal approach. The results of the study show that in order to strengthen the meaning of the constitutional life of Indonesian citizens and as a last resort for violations of citizens' constitutional rights, constitutional complaint authority needs to be given to the Constitutional Court as a form of constitutional supremacy in regulating people's sovereignty, because constitutional complaints are part of the problem of constitutional review. This is clearly stated in the spirit of the Preamble to the 1945 Constitution and is in line with the essence of the presence of the Constitutional Court of the Republic of Indonesia